2018
DOI: 10.30897/ijegeo.425606
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Mapping Using Sentinel-1A Synthetic Aperture Radar Data

Abstract: The aim of this study is to estimate and map soil moisture distribution using C-band Synthetic Aperture Radar (SAR) data. Sentinel-1A is a new generation C-band SAR satellite, and in this study Sentinel-1A data acquired on 24 April 2016 were used to retrieve soil moisture map. An agricultural region in Bergama, a district of İzmir city, was chosen as the study area. In-situ soil moisture measurements were carried out in 20 test fields simultaneously with SAR data acquisition. The effects of soil moisture and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 30 publications
0
16
0
2
Order By: Relevance
“…The statistical relation derived from the regression analysis to type. In [43], bare soil data with no vegetation have been used to propose a generalized model. The accuracy assessment has been conducted using 7 test sites, and the statistical metrics, namely R 2 and RMSE, were determined as 0.84 and 0.0246, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The statistical relation derived from the regression analysis to type. In [43], bare soil data with no vegetation have been used to propose a generalized model. The accuracy assessment has been conducted using 7 test sites, and the statistical metrics, namely R 2 and RMSE, were determined as 0.84 and 0.0246, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Estimation of soil moisture involved the testing of empirical models to present a correlation between measured soil moisture and predicted soil moisture derived from environmental covariates and backscattering coefficients with the aid of the ordinary least square (OLS) linear regression function [45]. Many researchers established empirical relationships to estimate soil moisture, and these models revealed that there is a fundamental relation between soil moisture and the backscattering coefficient [45][46][47][48][49].…”
Section: Estimation Of Soil Moisturementioning
confidence: 99%
“…Over the past four decades, several studies have shown the great potential of synthetic aperture radar (SAR) data for SSM mapping at an agricultural plot scale with high revisit time [5,[9][10][11][12]. Even though SAR data in the X-, C-and L-bands have been widely used in numerous research projects [13][14][15][16][17][18], only SAR data in the C-band are used today in operational approaches for SSM retrieving.…”
Section: Introductionmentioning
confidence: 99%
“…Figure12. Calculated error on the retrieved SSM using C-band real SAR data versus in situ measurements.…”
mentioning
confidence: 99%